Genetic relatedness and phylogenetic analysis of cryptocoryne species in Sarawak - Frankie, anak Lanying (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This systematic molecular study is conducted on fifteen Cryptocoryne (Araceae) species that were found in Sarawak including one which was collected from Kalimantan, Indonesia. These species were C. auriculata Engler, C. bullosa Engler, C. ferruginea Engler, C. fusca de Wit, C. keei Jacobsen, C. lingua Engler, C. pallidinervia Engler, C. striolata Engler, C. uenoi Y. Sasaki, C. zaidiana Ipor and Tawan, C. ciliata (Roxburgh) Schott var. latifolia Rataj, C. cordata Griffith var. zonata, C. longicauda Engler, C. purpurea Ridley and one unknown species, C. sp. This study is to determine genetic relatedness among species in the genus Cryptocoryne in Sarawak using random amplified polymorphic DNA (RAPD), and infer phylogenetic relationships from the coding regions of the rbcL and matK genes of the chloroplast DNA (cpDNA). Of the eighty decamer oligonucleotide primers used for RAPD analysis, only six primers (OPB-1, OPB-20, OPC- 6, OPC-15, OPD-5 and OPD11) produced distinct, reproducible and polymorphic amplified products. A total of eighty bands were amplified, with only one found to be monomorphic while 79 bands were polymorphic (98.75%), including four species- specific bands. Low genetic similarities between species were revealed ranging from 5.6% to 57.1%. Dendogram obtained from UPGMA analysis grouped the species into two clusters, with Cluster II further divided into several groups. The clustering pattern was found to be associated with chromosome numbers and slight similarities in leaf morphology. The interspecific relationship in the genus based upon the rbcL gene showed that the phylogenetic resolution has been poor as a result of low base substitution rates, whereas the matK gene showed a much higher rate. From the total aligned length of 1675 bp for matK, 210 variable sites (including 36 parsimony informative sites) were detected. Ten simple insertion / deletions (indels) of several lengths were also detected which could be identified as variations and potentially used for species identification. Between the two iv genes, matK gave more resolved phylogenetic trees, with strongly supported branches of the Bayesian tree (>0.95 PP). From the phylogenetic tree generated by matK, it was observed that the species were separated according to their chromosome number. Two clades were formed in the tree, with C. ciliata var. latifolia (x = 11) forming the independent lineage of Clade I and the rest forming Clade II. Clade II was further divided into two subclades, with species with the base chromosome x = 17 and 18, and x = 10 and 15 forming respective groups. The x = 17 and 18 has a wider distribution geographically as compared to species with x = 10 and 15, which were confined to only Borneo, Sumatra and Johor, and this was evident in the phylogenetic tree. Both rbcL and matK genes provided several congruent topologies in the phylogenetic trees, with C. keei, C. striolata and C. longicauda, and C. ferruginea, C. fusca and C. uenoi forming groups. This genus in Sarawak does not have any obvious morphological synapomorphies, having undergone adaptive radiation and island speciation, and therefore cannot provide a conclusive measure of genetic differences in reference to the morphological characteristics. With a majority of the species being endemics, the molecular data obtained in this study would be able to facilitate conservation aspects of the genus.